Prediction model of human comfort index in underground emergency refuge facilities - WANG Shu; JIN Long-zhe; OU Sheng-nan; LI Fang-wei; LI Jing (工程科学学报, 2015)
The psychology and physiology of miners would be damaged if they continue to stay in uncomfortable environments for long time. When waiting for rescue in emergency refuge facilities, numerous factors can affect comfortable feelings of miners. In this paper, four crucial factors, including oxygen concentration, carbon dioxide concentration, temperature and relative humidity, were selected as the study objects. Adopting the grading method, a series of human live experiments were performed to obtain vote data under both a single and multiple environmental variables. The functional relation between human comfort degree and environmental variables were got by statistically analyzing these vote data. A mathematical model was proposed to predict the human comfort degree of miners in refuge confined space. The allowable ranges of oxygen level, carbon dioxide level, temperature and relative humidity along with their controlling principles were discussed in the end.